Strategy Development Creative Industry EichhorniaCrassipesBag As a Superior Product of Lamongan Regency - M. Yaskun; Khoirul Hidayat (AIBPM Publisher, 2018)
Eichhorniacrassipes grow a lot of environment in Lamongan society. It has been a few years Lamongan community utilize plant eichhorniacrassipes for various crafts. Therefore it is necessary to do research on the development of creative industry eichhorniacrassipes bag. This research aims to design a strategy development creative industry eichhorniacrassipes bag so that the existence of creative industry eichhorniacrassipes bag can be developed. This research uses the SWOT method, by firstly identifying the strengths, weaknesses, opportunities, and threats of the eichhorniacrassipes bag industry. The results of this study indicate that industrial eichhorniacrassipes bag has a good market, but need to do some alternative strategies that are; market products through information technology, diversify products, cooperate with local governments and distributors. Keywords: Creative Industry,EichhorniaCrassipes Bag, Lamongan Regency